Course Conclusion paper about Bibliotherapy - Caldin, Clarice Fortkamp (Wydawnictwo eBooki.com.pl, 2015)
I. Introduction. II. Report of bibliotherapeutic activities as lecture conclusion task. II.1. Appliance of bibliotherapy in Centro Educacional Padre Jordan. II.2. Appliance of bibliotherapy to children in Centro de Educaçao Infantil Santo Antônio. II.3 Storytelling: bibliotherapeutic accomplished with children in Centro Comunitário Monte Verde. II.4. Appliance of bibliotherapy in Basic School Luiz Cândido da Luz. II.5. Bibliotherapy to welfare of old women in Lar Sao Francisco. III. Reflections.
Keywords: introspection; catharsis; identification; bibliotherapy